Electrolyte and lithium ion battery containing the same
By using the electrolyte formed by silicon imidazolyl compound and sulfonate compound in lithium-ion batteries, the problem of insufficient circulation performance of the silicon-based negative electrode sheet battery is solved, and a more stable SEI film and higher electrochemical performance are achieved.
Patent Information
- Application Number
- CN202211312996.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-25
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-10-25
AI Technical Summary
When using silicon-based negative electrode sheets, existing lithium-ion batteries have insufficient cycling performance and high-voltage performance, and silicon cracks lead to increased electrolyte solvent consumption and side reactions, affecting the battery life.
Using an electrolyte containing lithium salts, organic solvents and specific additives, including silicon imidazolyl compounds and sulfonate compounds, through which these additives form nitrogen-enriched inorganic layers and stable passivation layers in the electrolyte, Synergistically act to improve the component thickness and stability of the SEI film, inhibit silicon cracks and side reactions.
It significantly improves the cycle life and high-voltage performance of lithium-ion batteries, reduces the formation of "dead lithium" and the degree of decomposition of electrolyte, and enhances the first-circle efficiency and capacity retention rate of the battery.
Smart Images

Figure BDA0003907784620000021 
Figure BDA0003907784620000081 
Figure BDA0003907784620000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries and relates to an electrolyte and a lithium ion battery containing the electrolyte. Background Art
[0002] In today's society, people's demand for electronic digital devices and electric vehicles is constantly increasing, and the requirements for the energy storage industry are also constantly increasing. Lithium-ion batteries have attracted widespread attention in the market due to their superiority in energy density, power density, cycle life, etc. However, the graphite anode used in traditional lithium-ion batteries has basically reached its theoretical capacity limit, so it has been questioned in terms of energy density. In recent years, silicon-based and tin-based anodes with higher energy density have been developed and put into use one after another, but silicon-based materials are often accompanied by many interfacial side reactions, electrode pulverization, and too fast capacity decay during the lithium ion deintercalation process.
[0003] Means to improve high-energy silicon-based batteries include material compounding, pre-lithiation, optimized electrolyte design, and flexible processing of rigid electrodes. Since the first film formation has a huge impact on the silicon-based negative electrode, the thickness and composition of the SEI film are closely related to the performance decay of the electrode, so the regulation of the interface is particularly important. In order to improve the quality of SEI film formation, the optimization of electrolyte components is an important means that cannot be ignored. In particular, additives with strong functionality have been developed on a large scale. Additives are widely praised because they have a small dosage but can play a more obvious effect. Some additives with low LUMO values are widely used in silicon-based high-energy density batteries, such as fluoroethylene carbonate (FEC), vinylene carbonate (VC) and isocyanate, which have certain advantages in the film formation of silicon negative electrode batteries. FEC forms a thin SEI film rich in LiF at the interface, which can solve the problem of large consumption of silicon negative electrode electrolyte and has obvious advantages in improving the cycle.
[0004] The existing solvent system and additives can achieve a good solution when the silicon doping content is not high. However, as the requirements for energy density and power density continue to increase, when the negative electrode specific capacity reaches 700mAh / g, film-forming additives such as FEC and VC are not enough to meet the usage requirements, side reactions increase, the utilization rate of Si decreases, the proportion of "dead lithium" increases, and the cycle further deteriorates.
[0005] CN109888266A discloses a silicon-based negative electrode sheet, a preparation method thereof, and a lithium-ion battery. The negative electrode coating of the silicon-based negative electrode sheet provided by the invention includes a first coating located on the current collector and a second coating located on the first coating, the active material in the first coating includes a silicon-based negative electrode material, the active material in the second coating does not contain a silicon-based negative electrode material, and the surface of the second coating contains lithium. The silicon-based negative electrode sheet provided by the invention avoids direct contact between the silicon-based material and metallic lithium during the pre-lithiation process of the electrode sheet containing the silicon-based negative electrode material, and significantly improves the energy density and cycle stability. However, the cycle performance of the lithium-ion battery provided by the invention needs to be further improved.
[0006] Therefore, in the art, it is desired to develop an electrolyte that can improve the cycle performance of a lithium-ion battery when the negative electrode sheet of the lithium-ion battery is a silicon-based negative electrode sheet. Summary of the invention
[0007] In view of the shortcomings of the prior art, the object of the present invention is to provide an electrolyte and a lithium ion battery containing the same. When the negative electrode sheet of the lithium ion battery is a silicon-based negative electrode sheet, the electrolyte provided by the present invention can increase the compatibility with the silicon-based negative electrode sheet and improve the cycle performance of the lithium ion battery.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides an electrolyte, the electrolyte comprising a lithium salt, an organic solvent and an additive, the additive comprising a silicium imidazole compound and a sulfonate compound, the silicium imidazole compound having a structure shown in formula I, and the sulfonate compound having a structure shown in formula II:
[0010]
[0011] Among them, R 1 Any one selected from hydrogen, substituted or unsubstituted C1-C8 (e.g., C1, C2, C3, C4, C5, C6, C7 or C8) alkyl, substituted or unsubstituted C6-C18 (e.g., C6, C8, C10, C12, C14 or C18, etc.) aryl;
[0012] R 2 Any one selected from hydrogen, unsubstituted C1-C4 (e.g., C1, C2, C3 or C4) alkyl, borate, C1-C3 (e.g., C1, C2 or C3) oxygen ether alkyl, C1-C2 thioether alkyl;
[0013] R 3Any one selected from hydrogen, substituted or unsubstituted C1-C3 (e.g., C1, C2, or C3) chain alkyl, substituted or unsubstituted C3-C6 (e.g., C3, C4, C5, or C6) cycloalkyl, substituted or unsubstituted C6-C18 (e.g., C6, C8, C10, C12, C14, or C18, etc.) aryl;
[0014] R 4 , R 5 , R 6 Each is independently selected from any one of hydrogen, halogen, substituted or unsubstituted C1-C7 (e.g., C1, C2, C3, C4, C5, C6 or C7) alkane, methoxy, and ethoxy;
[0015] R 7 Any one selected from hydrogen, halogen, substituted or unsubstituted C1-C12 (e.g., C1, C2, C3, C4, C5, C6, C7, C8, C9, C10, C11, or C12) alkane, substituted or unsubstituted C2-C8 (e.g., C2, C3, C4, C5, C6, C7, or C8) alkene, substituted or unsubstituted C2-C5 (e.g., C2, C3, C4, or C5) alkynyl, substituted or unsubstituted C6-C18 (e.g., C6, C8, C10, C12, C14, or C18, etc.) aryl;
[0016] R 8 Any one selected from hydrogen, trimethylsilyl, triethylsilyl, substituted or unsubstituted C2-C11 (e.g., C2, C3, C4, C5, C6, C7, C8, C9, C10 or C11) alkane, substituted or unsubstituted C2-C7 (e.g., C2, C3, C4, C5, C6 or C7) olefin, substituted or unsubstituted C2-C6 (e.g., C2, C3, C4, C5 or C6) alkynyl, substituted or unsubstituted C6-C18 (e.g., C6, C7, C8, C10, C12, C14 or C18, etc.) aryl, substituted or unsubstituted sulfonic acid, 2H-pyranyl, 4H-pyranyl.
[0017] In the present invention, in order to form a passivation layer with uniform thickness on the negative electrode side of the lithium ion battery, silicon atoms with stable electronic layer structure are introduced into the electrolyte system, which not only have good compatibility with the negative electrode material, but also the imidazole groups connected to the silicon atoms can form an inorganic layer enriched with nitrogen at the interface, which can protect the SEI film during long-term circulation. However, the irreversible loss of lithium in the imidazole compound when the SEI is formed is large, and the addition of sulfonate compounds can greatly increase the proportion of active lithium, which will reduce the degree of decomposition of the electrolyte during the first oxidation process, and also have a certain inhibitory effect on the dissolution of positive electrode metal ions. Through the synergistic effect of the two, the thickness of the SEI film component can be controlled, the side reaction caused by the consumption of electrolyte solvent by silicon cracks can be suppressed, and the cycle life and high-voltage performance of lithium ion batteries using silicon-based negative electrode sheets as negative electrode sheets can be improved.
[0018] That is, the electrolyte provided by the present invention contains both a silicon imidazole compound and a sulfonate compound. The two additives act synergistically to improve the first-cycle efficiency of lithium-ion batteries, improve the shortcomings of poor cycle performance of high-energy-density silicon-based negative electrode batteries, and also have a certain inhibitory effect on the volume expansion of silicon-based negative electrodes.
[0019] Preferably, R 1 Any one selected from hydrogen, unsubstituted C1-C8 alkyl, C1-C5 halogenated alkyl, phenyl and biphenyl.
[0020] Preferably, R 3 Any one selected from hydrogen, substituted or unsubstituted C1-C3 chain alkyl, unsubstituted C3-C5 cycloalkyl, C3-C6 halogenated cycloalkyl and phenyl.
[0021] Preferably, R 4 , R 5 , R 6 Each is independently selected from any one of hydrogen, halogen, unsubstituted C1-C5 alkyl, C1-C7 halogenated alkyl, methoxy and ethoxy.
[0022] Preferably, R 7 Any one selected from hydrogen, halogen, unsubstituted C1-C12 alkyl, C1-C10 halogenated alkyl, substituted or unsubstituted C2-C8 alkene, substituted or unsubstituted C2-C5 alkynyl, unsubstituted phenyl, biphenyl and halogenated tolyl.
[0023] Preferably, R 8Any one selected from hydrogen, trimethylsilyl, triethylsilyl, unsubstituted C2-C11 alkyl, C2-C8 halogenated alkyl, substituted or unsubstituted C2-C7 olefin, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C6-C8 aryl, substituted sulfonic acid, 2H-pyranyl and 4H-pyranyl.
[0024] Preferably, the halogen is selected from any one of fluorine, chlorine, bromine or iodine, preferably fluorine.
[0025] In the present invention, "substituted" means substituted by one, two or more substituents selected from the following: halogen (fluorine, chlorine, bromine or iodine), C1-C6 (for example, it can be C1, C2, C3, C4, C5, C6) alkyl, C1-C3 (for example, it can be C1, C2, C3) alkoxy, C6-C18 (for example, it can be C6, C8, C10, C12, C14, C16 or C18) aryl.
[0026] Preferably, the silimidazole-based compound includes any one of trimethylsilimidazole, dimethylsilimidazole, 1-trifluoromethylsilimidazole, 1-trichloromethylsilimidazole, 1-trimethylsilyl-2-ethylimidazole, triethylsilimidazole, 1-triethylsilyl-4-boric acid methyl ester imidazole, 1-trimethylsilyl-2-phenylimidazole, 1-tert-butyldimethylsilimidazole, 1-trimethylsilyl-5-n-propyl imidazole, 1-dimethylsilyl-2-ethyl-4-phenylimidazole, 1-trimethylsilyl-4-fluoromethylimidazole or 1-dimethylethylsilimidazole, or a combination of at least two thereof.
[0027] Preferably, the sulfonate compound includes any one of phenyl fluorosulfonate, toluene fluorosulfonate, fluorophenyl fluorosulfonate, ethyl phenyl fluorosulfonate, trimethylphenyl fluorosulfonate, phenyl trifluoromethanesulfonate, ethyl trifluoromethanesulfonate, propargyl benzenesulfonate, p-toluenesulfonic anhydride, allyl vinyl sulfonic acid, methanesulfonic acid-2-propyn-1-ol, trimethylsilyl trifluoromethanesulfonate, 4-tetrahydropyranyl methanesulfonate or 3-butynyl p-toluenesulfonate, or a combination of at least two thereof.
[0028] Preferably, based on the mass of the electrolyte as 100%, the sum of the contents of the silimidazole-based compound and the sulfonate-based compound is 0.4% to 8.0%, for example, 0.4%, 0.6%, 0.8%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5% or 8.0%, etc.
[0029] Preferably, based on the mass of the electrolyte as 100%, the content of the silimidazole-based compound is 0.06% to 3.58%, for example, 0.06%, 0.09%, 0.18%, 0.35%, 0.55%, 0.73%, 1%, 1.5%, 1.9%, 2.1%, 2.8%, 3.2% or 3.4%, etc., and the content of the sulfonate-based compound is 0.02% to 2.89%, for example, 0.06%, 0.08%, 0.23%, 0.5%, 0.97%, 1.3%, 1.9%, 2.2%, 2.7% or 2.8%.
[0030] If the content of the silicium imidazole compound and the sulfonate compound is too low, the cycle performance of the lithium ion battery will not be significantly improved. If the content of the silicium imidazole compound and the sulfonate compound is too high, it will have an adverse effect on the interface.
[0031] Preferably, the additives further include general-purpose film-forming additives.
[0032] Preferably, the universal film-forming additive includes any one of fluoroethylene carbonate (FEC), diethylene sulfate (DTD), vinylene carbonate (VC) or difluoroethylene carbonate (DFEC) or a combination of at least two thereof.
[0033] Preferably, based on the mass of the electrolyte as 100%, the content of the universal film-forming additive is 2.6% to 13%, for example, 2.8%, 3.4%, 5.2%, 5.7%, 7.1%, 11.5%, 11.8%, 12.0%, 12.4%, 12.9% or 13.0%, etc.
[0034] Preferably, the lithium salt comprises lithium hexafluorophosphate (LiPF 6 ).
[0035] Preferably, the lithium salt further comprises any one of lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate or lithium difluorooxalophosphate or a combination of at least two thereof.
[0036] Preferably, based on 100% by mass of the electrolyte, the content of the lithium salt is 8.3% to 20.9%, for example, 9.2%, 11.4%, 13.5%, 14.1%, 15.2%, 17.7% or 19.0%.
[0037] Preferably, the mass ratio of the lithium hexafluorophosphate to any one of the lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium perchlorate or lithium difluorooxalate phosphate is 100:0.1 to 100:30.5, for example, 100:0.1, 100:0.5, 100:1, 100:5, 100:10, 100:15, 100:20, 100:25 or 100:30.5, etc.
[0038] Preferably, the organic solvent includes any one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl acetate (EA), 2,2-difluoroethyl acetate (DFEA) or acetonitrile (AN), or a combination of at least two thereof.
[0039] Preferably, based on 100% by mass of the electrolyte, the content of the organic solvent is 58.0% to 92.1%, for example, 58%, 60%, 65%, 68%, 79%, 83% or 91%.
[0040] In a second aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the electrolyte comprises the electrolyte as described in the first aspect.
[0041] Preferably, the negative electrode sheet is a silicon-based negative electrode sheet.
[0042] Preferably, the mass content of silicon in the silicon-based negative electrode sheet is 8.5% to 43.2%, for example, 8.7%, 9.1%, 12.0%, 17.3%, 21.2%, 23.0%, 28.0%, 30.0%, 35.0%, 38.0%, 40.0% or 43.0%, etc.
[0043] Preferably, the active material of the negative electrode sheet has a form comprising any one of nanoparticles, nanowires, nanospheres, nanowalls, 3D porous structures, carbon shell coatings, core-shell structures, layered structures, long-chain polymers or chain carbon, or a combination of at least two of these.
[0044] Preferably, the active material of the negative electrode sheet includes any one of silicon oxide compounds, silicon / aluminum oxide composites, silicon / indium tin oxide composites, silicon / cobalt oxide composites, silicon / carbon nanotube composites, silicon / graphene composites, silicon / graphene composites, silicon / copper oxide composites, silicon tin carbon composites, silicon lithium compounds or silicon oxide lithium compounds, or a combination of at least two thereof. In addition to the active material, the auxiliary materials include conductive agents, binders, etc. It should be emphasized that the gain effect brought by the present invention may be more obvious on silicon-based negative electrodes with higher energy density and higher specific energy, and the silicon content should not be limited to the range listed in the present invention.
[0045] Preferably, the morphology of the active material of the positive electrode sheet includes any one of a layered structure, a spinel structure, an olivine structure or an amorphous structure, or a combination of at least two thereof.
[0046] Preferably, the active material of the positive electrode sheet includes any one or a combination of at least two of lithium nickel compounds, lithium cobalt compounds, molybdenum disulfide, titanium dioxide, lithium manganese compounds, lithium rare earth metal compounds, phosphorus lithium compounds, lithium-rich compounds, copper manganese lithium compounds, nickel cobalt manganese compounds, nickel cobalt aluminum lithium compounds, nickel cobalt niobium lithium compounds, vanadium oxide compounds or conductive polymer compounds.
[0047] Compared with the prior art, the present invention has at least the following beneficial effects:
[0048] In the present invention, in order to form a passivation layer with uniform thickness on the negative electrode side of the lithium ion battery, silicon atoms with stable electronic layer structure are introduced into the electrolyte system, which not only have good compatibility with the negative electrode material, but also the imidazole groups connected to the silicon atoms can form an inorganic layer enriched with nitrogen at the interface, which can protect the SEI film during long-term circulation. However, the irreversible loss of lithium in the imidazole compound when the SEI is formed is large, and the addition of sulfonate compounds can greatly increase the proportion of active lithium, which will reduce the degree of decomposition of the electrolyte during the first oxidation process, and also have a certain inhibitory effect on the dissolution of positive electrode metal ions. Through the synergistic effect of the two, the thickness of the SEI film component can be controlled, the side reaction caused by the consumption of electrolyte solvent by silicon cracks can be suppressed, and the cycle life and high-voltage performance of lithium ion batteries using silicon-based negative electrode sheets as negative electrode sheets can be improved. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0050] Examples 1-13 and Comparative Examples 1-3
[0051] In Examples 1-13 and Comparative Examples 1-3, an electrolyte is provided respectively, wherein the electrolyte comprises a lithium salt, an organic solvent and an additive, wherein the additive comprises a silimidazole-based compound, a sulfonate-based compound and a general-purpose film-forming additive, and the specific selection and mass percentage (%) of each component of the electrolyte provided in each Example and Comparative Example are shown in Tables 1 and 2.
[0052] Table 1
[0053]
[0054]
[0055] Table 2
[0056]
[0057]
[0058] The blanks in Tables 1 and 2 indicate that the corresponding components were not added.
[0059] Application Example 1-13 and Comparative Application Example 1-3
[0060] In application examples 1-13 and comparative application examples 1-3, a lithium-ion battery is provided respectively. The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The electrolyte is the electrolyte provided in embodiment 1-13 and comparative example 1-3 respectively.
[0061] The preparation method of a lithium-ion battery comprises the following steps:
[0062] (1) Preparation of positive electrode sheet: Polyvinylidene fluoride (PVDF) was uniformly dissolved in N-methylpyrrolidone (NMP), and then the conductive agent Super P was added and mixed thoroughly. 8 Co 1 Mn 1 O 2 Powders are gradually added (LiNi 8 Co 1 Mn 1 O 2 The mass ratio of powder, PVDF and conductive agent Super P is 97.4:1.3:1.3 to obtain positive electrode slurry (the output solid content of the positive electrode slurry is 62.8%), the positive electrode slurry is coated on the current collector, and then dried, rolled and slit to obtain positive electrode sheets that can be directly stacked.
[0063] (2) Preparation of negative electrode sheets: Graphite, conductive carbon, silicon oxide powder, and sodium carboxymethyl cellulose in a mass ratio of 80.9:2.9:15:1.2 were premixed and stirred at a speed of 250 rpm for 140 min to obtain a negative electrode slurry. The negative electrode slurry was then transferred to deionized water for dispersion. After mixing evenly, the negative electrode slurry was sieved (180 mesh). Finally, the sieved negative electrode slurry was coated on the negative electrode collector, and then dried, rolled, and slit to obtain a negative electrode sheet that can be directly laminated.
[0064] (3) Preparation of electrolyte: The electrolyte (the filling gas is argon, and the gaseous water content is less than 10 ppm) is prepared in a Michelin glove box. First, organic solvents such as ethylene carbonate (EC), diethyl carbonate (EMC), ethyl methyl carbonate (DMC), and propylene carbonate (PC) are uniformly mixed in proportion. General film-forming additives and special additives (i.e., silimidazole compounds and sulfonate compounds) are added to the uniformly mixed solvent package. Finally, LiPF is added. 6, LiFSI and other lithium salts are mixed until there is no lithium salt residue at the bottom and the electrolyte is clear and not turbid, that is, an electrolyte with normal chromaticity is obtained, and stored in a -10°C refrigerator. The distribution ratios of each group are shown in Tables 1 and 2.
[0065] (4) Soft-pack battery cells: The positive and negative electrode sheets after stripping are stacked on a stacking machine. The separator is a three-layer material of PP / PE / PP to form a soft-pack battery cell.
[0066] (5) Liquid injection, formation and aging:
[0067] After the battery cell is dried at high temperature, the electrolyte of the embodiment and the comparative example is injected into the soft-pack battery cell. After the electrolyte is injected, the lithium battery is packaged for the first time, and the surface is cleaned to complete the preliminary work, and then placed at room temperature for one day. The formation is carried out by a step-by-step formation method. The first step is a formation current of 0.05C, and a constant current is charged for 2h. The second step is a formation current of 0.1C, and a constant current is charged until the voltage reaches 3.85V. After formation, it is aged at 50℃ for one day, cooled to room temperature, and finally sealed.
[0068] The performance test of the lithium-ion battery provided in the corresponding use case 1-13 and the comparative application example 1-3 is carried out as follows:
[0069] (1) Initial efficiency
[0070] The assembled lithium-ion battery is first subjected to formation, aging, capacity division and capacity determination operations to calculate the first cycle efficiency of the battery. The first charge capacity (formation + capacity division) is used as the denominator, and the divided first discharge capacity is used as the numerator. The value obtained by dividing is the first efficiency.
[0071] (2) Normal temperature cycle performance
[0072] After the capacity is fixed, the battery is charged and discharged at a constant current density of 1C of the rated capacity in a constant temperature room at 25℃ for 200 cycles, and the capacity retention rate and thickness expansion coefficient of the battery are observed. The capacity retention rate is calculated with the capacity before the first cycle as the initial value, as the denominator, and the capacity at the 200th week as the numerator, and then multiplied by 100%; the thickness expansion rate is calculated with the thickness before the first cycle as the initial value, as the denominator, and the thickness measured at the 200th week as the numerator, and then multiplied by 100%.
[0073] The performance test results are shown in Table 3.
[0074] Table 3
[0075]
[0076] It can be seen from Table 3 that the lithium-ion batteries provided by Application Examples 1-11 of the present invention all have higher initial efficiency (79%-92%), first 200-week capacity retention rate (87%-99%) and lower first 200-week thickness expansion rate (6%-12%).
[0077] Compared with Application Example 1, the electrolyte provided in Application Example 12 has a higher content of silicium imidazole compounds, which greatly reduces the initial efficiency of the lithium-ion battery; the electrolyte provided in Application Example 13 has a higher content of sulfonate compounds, which reduces the initial efficiency of the lithium-ion battery and deteriorates the cycle performance. This shows that excessive content of silicium imidazole compounds or sulfonate compounds in the electrolyte will deteriorate the performance of the battery, and the amount of additives needs to be controlled within a reasonable range.
[0078] Compared with Application Example 1, the initial efficiency of the lithium-ion battery provided by Comparative Application Example 1 is significantly reduced, the capacity retention rate of the lithium-ion battery provided by Comparative Application Example 2 in the first 200 weeks is significantly reduced, and the thickness expansion rate in the first 200 weeks is significantly increased, and the initial efficiency and the capacity retention rate of the lithium-ion battery provided by Comparative Application Example 3 are both significantly reduced, and the thickness expansion rate in the first 200 weeks is significantly increased. This shows that the synergistic effect of the silimidazole-based compound and the sulfonate-based compound can greatly improve the initial efficiency of the battery, significantly improve the cycle performance, and effectively control the thickness expansion rate.
[0079] The electrolyte provided by the present invention can build a stable electrochemical interface in a silicon-containing negative electrode battery. Under the anchoring effect of silicon atoms, the imidazole group and the sulfonic acid group can infiltrate more N / S elements into the interface protective film, increase more organic phase components, increase the proportion of active lithium, reduce the formation of "dead lithium", reduce the pulverization and volume expansion of silicon particles during the cycle, and help the positive and negative electrodes to form films, maintain low capacity decay, and improve their electrochemical performance.
[0080] The applicant declares that the present invention illustrates the electrolyte of the present invention and the lithium-ion battery containing the electrolyte through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. An electrolyte, characterized in that: The electrolyte includes a lithium salt, an organic solvent and an additive, wherein the additive includes a silimidazole-based compound and a sulfonate-based compound; The silimidazole-based compound includes any one of trimethylsilimidazole, dimethylsilimidazole, 1-trifluoromethylsilimidazole, 1-trichloromethylsilimidazole, 1-trimethylsilyl-2-ethylimidazole, triethylsilimidazole, 1-triethylsilyl-4-boric acid methyl ester imidazole, 1-trimethylsilyl-2-phenylimidazole, 1-tert-butyldimethylsilimidazole, 1-trimethylsilyl-5-n-propyl imidazole, 1-dimethylsilyl-2-ethyl-4-phenylimidazole, 1-trimethylsilyl-4-fluoromethyl imidazole or 1-dimethylethylsilimidazole, or a combination of at least two thereof; The sulfonate compound includes any one of phenyl fluorosulfonate, toluene fluorosulfonate, fluorophenyl fluorosulfonate, ethyl phenyl fluorosulfonate, trimethylphenyl fluorosulfonate, phenyl trifluoromethanesulfonate, ethyl trifluoromethanesulfonate, propargyl benzenesulfonate, p-toluenesulfonic anhydride, allyl vinyl sulfonic acid, 2-propynyl-1-methanesulfonate, trimethylsilyl trifluoromethanesulfonate, 4-tetrahydropyranyl methanesulfonate or 3-butynyl p-toluenesulfonate, or a combination of at least two thereof; Based on the mass of the electrolyte as 100%, the sum of the contents of the silimidazole-based compound and the sulfonate-based compound is 0.4% to 8.0%; Based on 100% of the mass of the electrolyte, the content of the silimidazole-based compound is 0.06% to 3.58%, and the content of the sulfonate-based compound is 0.02% to 2.89%.
2. The electrolyte according to claim 1, characterized in that The additives also include general-purpose film-forming additives; Based on the mass of the electrolyte being 100%, the content of the universal film-forming additive is 2.6% to 13%.
3. The electrolyte according to claim 1, characterized in that The lithium salt includes lithium hexafluorophosphate.
4. The electrolyte according to claim 3, characterized in that The lithium salt further comprises any one of lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium perchlorate or lithium difluorooxalophosphate or a combination of at least two thereof.
5. The electrolyte according to claim 1, characterized in that Taking the mass of the electrolyte as 100%, the content of the lithium salt is 8.3% to 20.9%.
6. The electrolyte according to claim 1, characterized in that The organic solvent includes any one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, ethyl acetate, 2,2-difluoroethyl acetate or acetonitrile, or a combination of at least two thereof; Taking the mass of the electrolyte as 100%, the content of the organic solvent is 58.0% to 92.1%.
7. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the electrolyte comprises the electrolyte according to any one of claims 1 to 6; The negative electrode sheet is a silicon-based negative electrode sheet.
8. The lithium-ion battery according to claim 7, characterized in that: The mass content of silicon in the silicon-based negative electrode sheet is 8.5% to 43.2%.
9. The lithium-ion battery according to claim 7, characterized in that: The active material of the negative electrode sheet includes any one of silicon oxide compounds, silicon / aluminum oxide composites, silicon / indium tin oxide composites, silicon / cobalt oxide composites, silicon / carbon nanotube composites, silicon / graphene composites, silicon / graphene composites, silicon / copper oxide composites, silicon-tin-carbon composites, silicon-lithium compounds or silicon-oxygen-lithium compounds, or a combination of at least two thereof.
Citation Information
Patent Citations
Silicon-based negative electrode plate, fabrication method thereof and lithium ion battery
CN109888266A
Electrolyte containing novel additive for lithium ion battery and lithium ion battery
CN110931865A
High-voltage lithium ion battery electrolyte film-forming additive, electrolyte and battery thereof
CN111900477A
